PENGARUH PERBANDINGAN UREA DAN PEG 1000 SERTA LAMA PERENDAMAN TERHADAP STABILISASI DIMENSI KAYU JABON (Anthocephalus cadamba Miq) - Misnawati Misnawati; Lusyiani Lusyiani; Kurdiansyah Kurdiansyah (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to analyze the effect of urea and PEG 1000 (Polyethylene glycol) on the success rate of Jabon wood stabilization (Anthocephalus cadamba Miq), Analyzing the effect of immersion duration on the success rate of Jabon wood dimension stabilization (Anthocephalus cadamba Miq). The method used that is a complete Random Design (RAL) by A factor of two (the concentration of the mixture of urea and PEG 1000) and B (long Soaking). The results of the urea and PEG 1000 studies have succeeded in which the values before the tangential treatment (control) with a value of 2.67% to 1.27%. While the radial value before treatment was 2.04% to 1.05%. While overall T/R depreciation gives the best value with values ranging from 1.0 -1.5. Treatment that produces the value of the best tangential direction i.e. ASE 70.32% in the mixture of urea and PEG 1000 0%-100%, long soaking 5 days (A5B3). While the value of ASE radial is said to succeed because more than 50% of the value of 66.06% urea mixture and PEG 1000 0%-100%, long soaking 5 days (A5B3). While ASE T/R can be said did not work because it is still less than 50% with the highest value 30.86% in the mixture of urea and PEG 1000 75%-25% with long submersion in 3 days (A4B2).Keywords: Immersion time, Urea, PEG 1000,Jabon